Potential plant proteins for functional food ingredients: Composition, utilization and its challenges - Paul Ndubuisi Anyiam; Suphat Phongthai; Lutz Grossmann; Young Hoon Jung; Samart Sai-Ut; Ekasit Onsaard; Saroat Rawdkuen (NFS Journal)
Increasing demand for sustainable and health-conscious food choices has driven a heightened search for alternative protein sources. Plant-based proteins are particularly emphasized for their nutritional benefits, sustainability, and versatility. However, the heavy dependence on soybean has hindered the diversification of plant-based protein sources for global food security amidst population growth. This review underscores the potential of plant protein sources for their novelty as functional food ingredients due to protein quality. These alternatives are also rich in diverse bioactive compounds that offer significant health benefits, positioning them for future food and nutraceutical applications. This review paper explores various potential sources such as rice bran, mung bean, jack bean, moringa seed, and bambara nut, evaluating their suitability based on compositions and amino acid profiles, for use in food formulations. It addresses the robust growth of the plant-based food market and the challenges hindering the full utilization of plant proteins as viable alternatives in shaping the future foods. By addressing gaps in knowledge about emerging plant protein sources, this review aims to enhance sustainability in the food system. Further research and development of alternative plant-based proteins can diversify food offerings while promoting environmental and human health considerations.